Pentingnya Pengembangan Karir Bagi Perempuan Di Masa Kini - Siregar , Muhammad Fuad Zaini (Saree: Research in Gender Studies, 2023)
This article examines the importance of careers for women. Changes in society's view of women in the world of work have brought about significant changes in women's participation in various sectors. Women's careers are seen as opportunities to increase women's economic empowerment, skills development, and social contribution. The research method used in this article is qualitative by taking a phenomenological approach. The stages of phenomenological analysis are participant selection, data collection, data transcription and exploration, excess identification, excess alignment and grouping, explanation and interpretation, and report preparation. The results of the study show that the importance of women's careers in the social and economic context is analyzed by considering the positive impact on the family, society, and gender equality. Career development is also linked to improving women's academics, helping change gender perceptions in society, and inspiring the younger generation. The importance of viewing women's careers as an aspect that is in line with religious values and the balance of roles in the family. Thus, women's career development is expected to make a significant contribution to economic empowerment, individual development, and social change, without neglecting their important role in the family and society.   Abstrak Penelitian ini mengulas tentang pentingnya karir bagi perempuan. Perubahan pandangan masyarakat terhadap perempuan di dunia kerja telah membawa perubahan yang signifikan terhadap partisipasi perempuan di berbagai sektor. Karier perempuan dipandang sebagai peluang untuk meningkatkan pemberdayaan ekonomi perempuan, pengembangan keterampilan, dan kontribusi sosial. Metode penelitian yang digunakan dalam artikel ini adalah kualitatif dengan menggunakan pendekatan fenomenologi. Tahapan analisis fenomenologi adalah pemilihan partisipan, pengumpulan data, transkripsi dan eksplorasi data, identifikasi kelebihan, penyelarasan dan pengelompokan kelebihan, penjelasan dan interpretasi, dan penyusunan laporan. Hasil penelitian menunjukkan bahwa pentingnya karir perempuan dalam konteks sosial dan ekonomi dianalisis dengan mempertimbangkan dampak positif terhadap keluarga, masyarakat, dan kesetaraan gender. Pengembangan karir juga dikaitkan dengan peningkatan kemampuan akademis perempuan, membantu mengubah persepsi gender di masyarakat, dan menginspirasi generasi muda. Pentingnya memandang karir perempuan sebagai aspek yang sejalan dengan nilai-nilai agama dan keseimbangan peran dalam keluarga. Dengan demikian, pengembangan karir perempuan diharapkan dapat memberikan kontribusi yang signifikan terhadap pemberdayaan ekonomi, pengembangan individu, dan perubahan sosial, tanpa mengabaikan peran pentingnya dalam keluarga dan masyarakat.